Analysis of Cambridge Curriculum Implementation in Character Education Aspects in Economic Learning (Case Study at Singapore Intercultural School Semarang) - Rafida Anindya; Heni Purwa Pamungkas (International Journal of Emerging Research and Review, 2023)
Objective: This study aims to analyze the implementation of Cambridge curriculum in the field of Economic and to find out the implications for developing student’s character. Method: This research is conducted at Singapore Intercultural School (SIS) Semarang and carried out by interview, observation and documentation. The validity technique used is triangulation. Results: The results showed that the implementation of Cambridge Curriculum at SIS Semarang is very high in terms of the planning, implementation, and evaluation stages of learning, and has integrated character education through aspects of school input, process, and output. Novelty: This study combines educational character variables in the Cambridge International Curriculum and the Indonesian National Curriculum with research objects in international schools.